Application of The Problem-Based Learning Model to Improve Mathematical Communication Ability of Senior High School Students - Silmi Ghaida; Al Jupri (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
Mathematical communicative competence constitutes a pivotal pillar within the architecture of mathematics education. Nevertheless, empirical realities across Indonesian classrooms disclose a disquieting deficit in learners’ capacity to articulate mathematical reasoning with clarity and precision. This inquiry is undertaken to ascertain whether the attainment and progressive enhancement of students’ mathematical communication proficiency, when cultivated through a Problem-Based Learning paradigm, surpass those fostered under conventional instructional approaches. Anchored in a quantitative framework, the study employs a quasi-experimental methodology, operationalized through a pretest–posttest non-equivalent group design to capture comparative developmental trajectories between cohorts. The participants were tenth-grade students from a senior high school in Bandung City, with two classes deliberately designated as samples through purposive selection. Data collection relied on written assessments targeting mathematical communicative competence and observational checklists as supporting instruments. The findings disclosed that: (1) learners immersed in the Problem-Based Learning approach attained a more elevated level of mathematical communicative performance than those instructed conventionally; and (2) the extent of their developmental gain likewise outstripped that of their peers in the traditional classroom context.